Mean hydraulic retention time and pathways flow simulation through out a physical model for a WSPs and an UASB - Aldana, Gerardo; Pérez, Jhonny (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
Wastewater Treatment Plant Works has been facing hydraulic problem refers to back-mixing, short-circuiting and wind effect, thus reducing of the Mean Hydraulic Retention Time, MHRT. Tracer studies for full-scale WSP and UASB is complex and expensive. For that, a calibrated physical model, PM is better alternative to determine MHRT even though similarities between prototype and physical model are achieved. The aim of this study is to determine the MHRT through out two physical models by using Rhodamine WT dye and LiCl then it was compared with one obtained previously from the prototype. The methodology was the construction and calibration of the models scale reduced 1:18 and 1:90 from prototype (maturation pond, Lidsey UK) and (UASB, Colombia), respectively. Hydraulic pathways using tracer’s techniques in still and artificial solution water was analysed. The results found an agreement of the layout match in terms of MHRT (0.77d against to 0.89d) for WSPs and (4,8h against to 6.17) for an UASB between P.M and prototypes over 96% of confidence level. Dispersed-mixed flow was achieved.